A Combination Strategy to Inhibit Pim‐1: Synergism between Noncompetitive and ATP‐Competitive Inhibitors. Issue 3 (22nd February 2013) - Mori, Mattia; Tintori, Cristina; Christopher, Robert Selwyne Arul; Radi, Marco; Schenone, Silvia; Musumeci, Francesca; Brullo, Chiara; Sanità, Patrizia; Delle Monache, Simona; Angelucci, Adriano; Kissova, Miroslava; Crespan, Emmanuele; et al.
Abstract Pim‐1 is a serine/threonine kinase critically involved in the initiation and progression of various types of cancer, especially leukemia, lymphomas and solid tumors such as prostate, pancreas and colon, and is considered a potential drug target against these malignancies. In an effort to discover new potent Pim‐1 inhibitors, a previously identified ATP‐competitive indolyl‐pyrrolone scaffold was expanded to derive structure–activity relationship data. A virtual screening campaign was also performed, which led to the discovery of additional ATP‐competitive inhibitors as well as a series of 2‐aminothiazole derivatives, which are noncompetitive with respect to both ATP and peptide substrate. This mechanism of action, which resembles allosteric inhibition, has not previously been characterized for Pim‐1. Notably, further evaluation of the 2‐aminothiazoles indicated a synergistic inhibitory effect in enzymatic assays when tested in combination with ATP‐competitive inhibitors. A synergistic effect in the inhibition of cell proliferation by ATP‐competitive and ATP‐noncompetitive compounds was also observed in prostate cancer cell lines (PC3), where all Pim‐1 inhibitors tested in showed synergism with the known anticancer agent, paclitaxel. These results further establish Pim‐1 as a target in cancer therapy, and highlight the potential of these agents for use as adjuvant agents in the treatment of cancer diseases in which Pim‐1 is associated with chemotherapeutic resistance.